Late Clinical Outcomes of the Fontan Operation in Patients with Tricuspid Atresia - Mastalir,Eduardo T. (2002)
OBJECTIVE: Evaluation of the long-term clinical results of the Fontan operation in patients with tricuspid atresia. METHODS: A retrospective analysis was made at the Instituto de Cardiologia do Rio Grande do Sul (Institute of Cardiology of Rio Grande do Sul), from August 1980 through January 2000, of 25 patients with a long-term follow-up, out of a series of 36 patients who underwent the Fontan operation or one of its variants due to tricuspid atresia. Their mean age at surgery was 5.4±3.1 years, and their mean weight was 15.8±6.1 kg, the majority of them (63.9%) being males. Four patients underwent the classical Fontan operation, 12 the Kreutzer variant, 6 the Björk variant, 9 total cavopulmonary shunt with a fenestrated tube, and 5 total cavopulmonary shunt with a nonfenestrated tube. RESULTS: The patients were followed-up on an outpatient basis, with a mean long-term survival time of 5.5±4.2 years (50 days to 17.8 years) and a late mortality rate of 8%. Arterial saturation increased from 77.2±18.8% in the preoperative period to 91±6.7% upon the last outpatient visit (p>0.05). At the final check, most (67%) patients were asymptomatic and 87% could tolerate exercise. Ten (40%) patients experienced some kind of complication during the long-term follow-up, such as cardiac arrhythmia, cyanosis, protein-losing enteropathy, neurological events, right heart failure, intolerance to exercise and reoperation. CONCLUSION: The results indicate that, once the immediate postoperative period is over, during which the adaptations to the new circulatory physiology occur, the evolution of patients with tricuspid atresia who underwent the Fontan operation is satisfactory, in spite of a low, yet significant, morbidity.